Nontargeted Metabolomics of Streptomyces Sourced from Thailand Reveals the Presence of Bioactive Metabolites - Sunghanghwa, Yuwathida; Paemanee, Atchara; Do, Kiep Minh; Meethangdee, Mathurin; Plechatá, Michaela; Pathom-Aree, Wasu; Punsawad, Chuchard; Morita, Hiroyuki; Tangphatsornruang, Sithichoke; Kamenik, Zdenek; Jaisi, Amit (ACS omega, 2025)
Actinobacteria are widely recognized as prolific producers of bioactive metabolites with diverse biological properties, yet they remain largely unexplored. In this study, we investigated the antimicrobial potential and chemical diversity of crude extracts from actinobacterial strains isolated from mangrove sediments collected in Chonburi and Chachoengsao provinces of Thailand. Taxonomic identification confirmed that these isolates belong to the genus Streptomyces. Notably, ten isolates, identified as Streptomyces iranensis, Streptomyces yogyakartensis, Streptomyces cacaoi, Streptomyces ardesiacus, Streptomyces phaeoluteichromatogenes, and Streptomyces albiaxialis, exhibited potent inhibitory activity against chloroquine-resistant Plasmodium falciparum K1 at concentrations <10 μg/mL. Among these, only S. albiaxialis displayed anti-human immunodeficiency virus-1 viral protein R (HIV-1 Vpr) activity in HeLa cells harboring the TREx plasmid encoding full-length Vpr (TREx-HeLa-Vpr cells). MS/MS-guided molecular networking analysis highlighted the metabolic complexity of the isolates, revealing a diverse array of distinct compounds. These included chymostatin B, geldanamycin, dehydroxynocardamine, ikarugamycin epoxide, kanchanamycin C, glochidone, bisucaberin, coproporphyrin III, futalosine, and various siderophores such as ferrioxamine B, desferrioxamine D2, desferrioxamine G, desferrioxamine E, desferrioxamine, desferrioxamine H, and ferrioxamine E. Moreover, guided by the potent antimalarial activity of strain S2-SC19, the compound elaiophylin was detected, isolated, and identified using analytical techniques. Remarkably, the compound exhibited potent antimalarial activity with an IC50 value of 0.002 ± 0.002 μg/mL against P. falciparum K1. Furthermore, genomic analysis revealed that strain S2-SC19 is most closely related to Streptomyces asiaticus DSM no. 41761. This study highlights Thai mangrove soil as a valuable source of bioactive compounds, including elaiophylin, and underscores the bioactive potential and chemical diversity of mangrove ecosystems as a rich, untapped reservoir of natural products.